Procedure for increased recovery of Campylobacter jejuni from inoculated unpasteurized milk. - Koidis, P (1984)
Different treatments were applied to Campylobacter jejuni-inoculated unpasteurized milk to identify means of enhancing the survival of the organism in refrigerated (4 degrees C) samples. The greatest survival occurred in milk supplemented with 0.01% sodium bisulfite and held under an atmosphere of 100% nitrogen (bisulfite-nitrogen), in most instances allowing isolation of C. jejuni from highly contaminated milk 15 or more days longer than from unsupplemented milk held in air (21% oxygen). Although a larger amount of Campylobacter was consistently recovered from milk treated with bisulfite-nitrogen, similar isolation rates (qualitative) resulted from milk stored in air and supplemented with 0.01% sodium bisulfite and 0.15% sodium thioglycolate when analyzed within 12 days after sampling. Milk samples to be transported and assayed at a later date would best be held refrigerated (4 degrees C) and supplemented with 0.01% sodium bisulfite and either 0.15% sodium thioglycolate or an atmosphere of 100% nitrogen.